Cover Image. Issue 3 (22nd June 2020) - Unknown
Abstract : Polarized optical microscopy images of PEO‐ b ‐PCL films crystallized under different conditions, including the cast from different solvents and melt‐recrystallization. Clockwise from the top left of the image from Van Horn and colleagues (page e10107), the solvents used were chloroform, toluene, melt recrystallization, and THF. Due to differences in crystal growth rate, PEO exhibits large spherulites, while PCL spherulites are smaller. The choice of solvent influenced the morphology developed during drying/crystallization because of selective solvation of one block or the other. Toluene cast crystals exhibit no birefringence indicating a transition to flat‐on instead of edge‐on crystals. Crystals grown from THF exhibit an irregular pattern. Similar morphologies were observed for symmetric and asymmetric PEO‐ b ‐PCL. (doi.org/10.1002/pcr2.10107 ) Abstract : Polarized optical microscopy images of PEO‐ b ‐PCL films crystallized under different conditions, including the cast from different solvents and melt‐recrystallization. Clockwise from the top left of the image from Van Horn and colleagues (page e10107), the solvents used were chloroform, toluene, melt recrystallization, and THF. Due to differences in crystal growth rate, PEO exhibits large spherulites, while PCL spherulites are smaller. The choice of solvent influenced the morphology developed during drying/crystallization because of selective solvation of one block or the other. Toluene cast crystals exhibit no birefringence indicating a transition to flat‐on instead of edge‐on crystals. Crystals grown from THF exhibit an irregular pattern. Similar morphologies were observed for symmetric and asymmetric PEO‐ b ‐PCL. (doi.org/10.1002/pcr2.10107 )